Temporal trends in childhood mortality in Ghana: impacts and challenges of health policies and programs. Issue 1 (1st December 2016) - Kayode, Gbenga A.; Grobbee, Diederick E.; Koduah, Augustina; Amoakoh-Coleman, Mary; Agyepong, Irene A.; Ansah, Evelyn; van Dijk, Han; Klipstein-Grobusch, Kerstin
Abstract : Background: Following the adoption of the Millennium Development Goal 4 (MDG 4) in Ghana to reduce under-five mortality by two-thirds between 1990 and 2015, efforts were made towards its attainment. However, impacts and challenges of implemented intervention programs have not been examined to inform implementation of Sustainable Development Goal 3.2 (SDG 3.2) that seeks to end preventable deaths of newborns and children aged under-five. Thus, this study aimed to compare trends in neonatal, infant, and under-five mortality over two decades and to highlight the impacts and challenges of health policies and intervention programs implemented. Design: Ghana Demographic and Health Survey data (1988–2008) were analyzed using trend analysis. Poisson regression analysis was applied to quantify the incidence rate ratio of the trends. Implemented health policies and intervention programs to reduce childhood mortality in Ghana were reviewed to identify their impact and challenges. Results: Since 1988, the annual average rate of decline in neonatal, infant, and under-five mortality in Ghana was 0.6, 1.0, and 1.2%, respectively. From 1988 to 1989, neonatal, infant, and under-five mortality declined from 48 to 33 per 1, 000, 72 to 58 per 1, 000, and 108 to 83 per 1, 000, respectively, whereas from 1989 to 2008, neonatal mortality increased by 2 per 1, 000 while infant and under-five mortality further declined by 6 per 1, 000 and 17 per 1, 000, respectively. However, the observed declines were not statistically significant except for under-five mortality; thus, the proportion of infant and under-five mortality attributed to neonatal death has increased. Most intervention programs implemented to address childhood mortality seem not to have been implemented comprehensively. Conclusion: Progress towards attaining MDG 4 in Ghana was below the targeted rate, particularly for neonatal mortality as most health policies and programs targeted infant and under-five mortality. Implementing neonatal-specific interventions and improving existing programs will be essential to attain SDG 3.2 in Ghana and beyond.